Conflito de gerações: o expressionismo e Christoph Meckel - Dornbusch, Claudia (In:Pandaemonium Germanicum;São Paulo : Humanitas Publicações, 1997-2006;Band 1, Heft 1 (1997), Seite 87-96;22 cm, 1997)
In this article, we try to identify characteristics of German Expressionism in contemporary literature and its possible variations. The focus will be on the generation conflict and the text
urn:nbn:de:hebis:30:3-259625
Keywords: Online-Publikation; Meckel; Christoph; Suchbild; Expressionismus; Generationskonflikt